A single inhaler triple therapy fluticasone furoate/umeclidinium/vilanterol for the treatment of COPD. Issue 3 (4th March 2022) - Cazzola, Mario; Rogliani, Paola; Calzetta, Luigino; Ora, Josuel; Matera, Maria Gabriella
ABSTRACT: Introduction: Single inhaler triple therapy (SITT) with an inhaled corticosteroid, a long-acting β2 -agonist, and a long-acting muscarinic antagonist is an effective and attractive therapeutic option codified in the recommendations of guidelines and treatment strategies for the management of COPD. Areas covered: The preclinical and clinical development in COPD of fluticasone furoate (FF)/umeclidinium (UMEC)/vilanterol (VI) SITT and its use in the real world. Expert opinion: Findings from phase III/IV trials and the use of FF/UMEC/VI in the real-world setting support the view that it may be a useful, safe, and cost-effective option for the maintenance treatment of COPD, especially when dealing with patients who are not adequately controlled with dual ICS/LABA or LAMA/LABA therapy. Only direct head-to-head comparisons will be able to establish whether FF/UMEC/VI may be preferable to the other SITTs approved for COPD due to its pharmacokinetic and pharmacodynamic characteristics and especially the fact that it is the only one that can be taken once-daily. In addition, there is a need for further studies, especially in the real world, to optimize the positioning of FF/UMEC/VI in the treatment of COPD, also considering the availability of FF/VI and UMEC/VI and the need for better differentiation between the three treatments.